Literature Review: Clinical Trial on the Effectiveness of Melatonin as an Alternative Medicine for COVID-19 - Ibnu Mukti, Galih; Laily Hilmi, Indah; Salman, Salman (Jurnal EduHealth, 2022)
Pandemic COVID-19 is one of the horrific events in history. It has leaves awareness of the need for more effective, cheap, and widely available drugs such as melatonin. In this literature review will discuss the effectiveness of melatonin against COVID-19 by reviewing clinical trial research conducted abroad with the aim of providing information that melatonin can be used in Indonesia for COVID-19 treatment therapy.